Community Empowerment with Training in the Making of Spice Tea Beverages in Banjaragung Village, Tuban District - Abdul Khafid Maulana; Muhammad Yusuf; Hendra suwardana; Miftachul Munir; Fiki Andriyan (OJS Universitas Muhammadiyah Gresik, 2021)
Community Service is one of the Tri dharmas of Higher Education to be one of the accesses to achieve this vision. The community in Banjaragung Village was chosen as a partner to introduce Health Tea drinks made from pure spices. Through this activity, the author hopes to be able to carry out the mission to realize the learning process in the field of creative economic entrepreneurship with qualities that are relevant to the needs of today's society. Spices and especially sappan wood in Banjaragung Village have not been processed properly and lacked innovation. Considering that today's society needs drinks and food that can increase the body's immune system with spices, community service is made to make training to process secang wood and spices such as red ginger, lemongrass, cinnamon and tea leaves into products that are quickly consumed. by making health tea bags. Secang wood plant or the Latin nameCaesalpinia sappan is one type of spice that can be used for its woody stems or fruit. The components of bioactive compounds contained inwood, namely brazilian, brazilein, 3'-O-methyl braziline, sappansappan, chalcone, sappancalchone are known as antioxidants. Research on sappan wood as an antioxidant and can be used as a natural dye has been a lot. The counseling carried out is expected to provide insight to the community in Banjaragung Village about how to make Health Tea drinks so that they can help improve the economic level of the community.